The European Union (EU) Political Identity within the migrant crisis, and the Balkan – Bosnian route; xenophobia and religious identity (Research, Society and Development, 2020)
The study aims to critically analyze the EU's political identity and how the migrant crisis embodies the most challenging political issue facing the E.U., implicating growing xenophobia and questioning European multiculturalism. Moreover, the author provides insight into the migrant crisis's socio-political and security challenges, followed by ethnographic research of the migrant's religious identity within the Balkan route. Migrations are a central issue for Europe's future, security, and identity. The EU's cultural integrity remains unclear, and the migrant crisis opens up a multiculturalism discourse. The nation-state model has undergone significant globalized world changes, becoming less sustainable and less critical for cultural, political, and economic processes. Due to the growing economic insecurity and the fear of losing national identities in an environment of globalized culture, some have perceived multiculturalism as a threat. The humanitarian and security discourse reflects the micro-level of the situation on the ground and the mass media's macro levels and political action. Acceptance of ethnoreligious or political diversity does not relieve immigrants of the duty to recognize all the rules necessary to conduct productive coexistence. Migrants' participation in socio-economic and political systems means realizing the preconditions for the beginning of cultural integration. The crisis triggered an avalanche of anti-Islam sentiments that became a reference matrix for radical populism. The sense of identification with the housing society-Bosniaks, where Islamic regulations on the matrix are legitimized by recognizing a universal theological pattern, is a symbolic moment and a participative approach to understanding both religion and integration. Constructing immigrants as a group, whether they are migrants, refugees, or asylum seekers, tends to encourage the perception that "their "interests, values, and traditions are competing with "ours, "stimulating negative emotions in the form of prejudice.